Small interfering RNA (siRNA) as a potential gene silencing strategy for diabetes and associated complications: challenges and future perspectives - Waghode, Pranali; Quadir, Sheikh Shahnawaz; Choudhary, Deepak; Sharma, Sanjay; Joshi, Garima (Journal of diabetes and metabolic disorders, 2024)
Objective This article critically reviews the recent search on the use of Small Interfering RNA (siRNA) in the process of gene regulation that has been harnessed to silence specific genes in various cell types, including those involved in diabetes complications. Significance Diabetes, a prevalent and severe condition, poses life-threatening risks due to elevated blood glucose levels. It results from inadequate insulin production by the pancreas or ineffective insulin utilization by the body. Recent research suggests siRNA could hold promise in addressing diabetes complications. Methods In this review, we discussed several subjects, including diabetes; its function, and common treatment options. An in-depth analysis of gene silencing method for siRNA and role of siRNA in diabetes, focusing on its impact on glucose homeostasis, diabetic retinopathy, wound healing, diabetic nephropathy and peripheral neuropathy, diabetic foot ulcers, diabetic atherosclerosis, and diabetic cardiomyopathy. Result siRNA-based treatment has the potential to target specific genes without disrupting several other endogenous pathways, which decreases the risk of off-target effects. In addition, siRNA has the capability to provide long-term efficacy with a single dose which will reduce treatment options and enhance patient compliance. Conclusion In the context of diabetic complications, siRNA has been explored as a potential therapeutic tool to modulate the expression of genes involved in various processes associated with diabetes-related issues such as Diabetic Retinopathy, Neuropathy, Nephropathy, wound healing. The use of siRNA in these contexts is still largely experimental, and challenges such as delivery to specific tissues, potential off-target effects, and long-term safety need to be addressed. Additionally, the development of siRNA-based therapies for clinical use in diabetic complications is an active area of research.